2018
DOI: 10.2131/jts.43.587
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study for carcinogenicity of 7 different multi-wall carbon nanotubes with different physicochemical characteristics by a single intraperitoneal injection in male Fischer 344 rats

Abstract: The present study comparatively examined carcinogenicity of 7 different multi-wall carbon nanotubes (MWCNTs) with different physicochemical characteristics. Physicochemical characteristics of MWCNTs (referred to as M-, N-, WL-, SD1-, WS-, SD2-and T-CNTs in the present study) were determined using scanning electron and light microscopes and a collision type inductively coupled plasma mass spectrometer. Male Fischer 344 rats (10 weeks old, 15 animals per group) were administered MWCNTs at a single intraperitonea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…MWCNTs can be divided into two general subtypes: tangled and straight. Studies in rats using intraperitoneal injection of straight-type MWCNTs [15][16][17][18], an intermediate-type of MWCNT [18], and tangled-type MWCNTs [14][15][16][17] showed that in the peritoneal cavity the straight-type MWCNTs had the highest carcinogenic potential, the intermediate type MWCNT had a lower carcinogenic potential than the straight-type MWCNTs, and the tangled-type MWCNTs had the lowest carcinogenic potential. Two of these studies used MWCNTs with diameters similar to the MWCN T-A used in our present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MWCNTs can be divided into two general subtypes: tangled and straight. Studies in rats using intraperitoneal injection of straight-type MWCNTs [15][16][17][18], an intermediate-type of MWCNT [18], and tangled-type MWCNTs [14][15][16][17] showed that in the peritoneal cavity the straight-type MWCNTs had the highest carcinogenic potential, the intermediate type MWCNT had a lower carcinogenic potential than the straight-type MWCNTs, and the tangled-type MWCNTs had the lowest carcinogenic potential. Two of these studies used MWCNTs with diameters similar to the MWCN T-A used in our present study.…”
Section: Discussionmentioning
confidence: 99%
“…The iron content of MWCNT-A and MWCNT-B is strikingly different: MWCNT-A has an iron content of approximately 0.001% while MWCNT-B has an iron content of 1.1%, a difference of more than 1000-fold. While iron content has not been found to be associated with MWCNT induction of mesothelial tumors in the peritoneal cavity [17], it is possible that iron content may have a role in MWCNT-mediated carcinogenicity in the lung [28]. Another notable difference between MWCNT-A and MWCNT-B fibers is the number of coaxial graphene cylinders that compose the fibers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The carcinogenic rates of four needle-shaped MWCNTs were as high as 100% while tangled MWCNTs did not induce mesothelioma. 190 Comprehensive findings from multiple studies thus suggest that different shapes of CNTs exert differing levels of cytotoxicity, with the greatest toxicity induced by needle-shaped CNTs.…”
Section: Shapementioning
confidence: 99%
“…[17] CNTs also suffer from controversial results and concerns associated with their cytotoxicity as biointerfaces. [18][19][20] The sheet resistance (Rsh) of graphene and CNTs is typically 1-2 orders of magnitude higher than that of ITO. [12,14] As a result, graphene and CNTs microelectrodes require additional metal interconnects which complicates the device manufacturing process.…”
Section: Introductionmentioning
confidence: 99%